Nfe2l1 dysfunction alters Parkinson’s disease-related gene expression and impairs neuronal differentiation under ubiquitin stress in neuronal differentiated P19 Cells - Hossein Khodadadi; Dawid Winiarczyk; Kamila Łuczyńska; Hiroaki Taniguchi (Scientific Reports)
Abstract Proteostasis is essential for neuronal health, and its disruption is implicated in neurodegenerative diseases such as Parkinson’s disease (PD). Nfe2l1, a key regulator of proteostasis and ubiquitination, plays a significant role in neuronal health, yet its molecular functions in neuronal cells remain unclear. Our study investigates the role of Nfe2l1 in RA-induced neuronal differentiation of P19 cells under proteasome inhibition. This condition significantly increased Nfe2l1 expression at both protein and RNA levels in wild-type and differentiated cells. In differentiated cells under proteasome inhibition, RNA sequencing revealed an enrichment of neurodegenerative pathways, particularly those associated with PD. Proteasome inhibition led to the upregulation of several PD-related genes, including Atf6, Camk2d, and Sod1. However, Nfe2l1 knockdown in differentiated cells significantly reduced the expression of these genes, highlighting the role of Nfe2l1 in the regulation of PD-related pathways. Knockdown of Nfe2l1 also decreased Neat1, a long non-coding RNA associated with PD pathology, and downregulated the neuronal marker Map2, indicating impaired neuronal differentiation. Furthermore, Nfe2l1 knockdown increased ubiquitination under proteasome inhibition, emphasizing its role in protein degradation and neuronal homeostasis under stress. These findings highlight Nfe2l1 as a critical regulator in neuronal cells and reveal its potential role in maintaining proteostasis and involvement in neurodegenerative disease mechanisms, such as PD.